Problematika Aturan Pemungutan Suara Ulang dalam Perselisihan Hasil Pemilu Presiden dan Wakil Presiden - M Rizqi; Didan Neofal Arysandi (Fakultas Hukum, Universitas Warmadewa, 2024)
The issue of unclear regulations regarding the implementation of Repeat Voting (PSU) in the presidential and vice-presidential elections has become a significant challenge in ensuring a fair electoral process. The current regulations, particularly Law No. 7 of 2017 on Elections and PKPU Regulation No. 25 of 2023, exhibit inconsistencies, leading to legal uncertainty when PSU involves more than two candidate pairs. This study aims to analyze the gap between theory and practice in the implementation of PSU, especially in cases that result in legal ambiguity. Using a normative juridical method, this research critically examines relevant laws, court rulings, and doctrinal studies to identify key areas in need of regulatory reform. The findings reveal that the lack of harmonization between regulations poses difficulties for electoral authorities in conducting PSUs. Additionally, inadequate guidance and the absence of clear technical directives hinder PSU implementation, potentially compromising the integrity of elections. The study concludes that amendments to the Election Law are urgently needed to ensure that PSU can be conducted effectively and efficiently, thus reducing potential legal issues in future elections.